Pozaantenowe formy rozrywki jako dopełnienie przekazów stacji radiowych w Polsce - Czarnek, Paulina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The situation on the contemporary media market, including radio, has led to the building of a radio network’s value becoming more than just the result of an interesting programme offer that meets listeners’ needs. Listeners also desire other elements that strengthen their attachment to a particular brand. For this reason, radio broadcasters quite often prepare for listeners different forms of entertainment that take place outside the radio studio; examples include summer concert tours, trips to well-known health resorts during winter and summer holidays, New Year’s Eve parties, special-occasion concerts, football matches, etc. This article is a review of entertainment offers that are part of a strategy of interaction with the audience outside of the radio studio and an attempt to evaluate their influence on building the market position of a radio brand.